2002
DOI: 10.1590/s1516-35982002000400002
|View full text |Cite
|
Sign up to set email alerts
|

Farinha de vísceras de aves em rações para alevinos de tilápia do Nilo,Oreochromis niloticus (L.)

Abstract: RESUMO -Este estudo foi conduzido com o objetivo de avaliar o desempenho e as características de carcaças de alevinos de tilápia do Nilo (Oreochromis niloticus) submetidos a rações com níveis de inclusão de farinha de vísceras (FV), assim como os coeficientes de digestibilidade aparente (CDA) dos nutrientes deste alimento. Para o experimento de desempenho, foram utilizados 300 alevinos, com peso inicial médio de 0,35 ± 0,01 g, distribuídos em trinta tanques-rede (120 L), instalados em cinco tanques (1000 L). F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
0
3
0
4
Order By: Relevance
“…However, different results have been obtained by HASSANI et al ( 2021), who have found a higher rate for this variable by replacing 100% fish meal with poultry by-product meal in the diets of sturgeon juveniles. FARIA et al (2002), when analyzing (0, 4, 8, 12, 16, and 20%) the inclusion of poultry by-product meal in the diets of Nile tilapia fingerlings, have obtained a quadratic effect, which shows a better conversion for the level of 20% of inclusion. SIGNOR et al (2007) have found (for 0, 5, 10, 15, and 20% of this same ingredient) a linear decrease, and the level of 20% of inclusion of poultry by-product meal resulted in the best feed conversion for Leporinus macrocephalus juveniles.…”
Section: Resultsmentioning
confidence: 94%
“…However, different results have been obtained by HASSANI et al ( 2021), who have found a higher rate for this variable by replacing 100% fish meal with poultry by-product meal in the diets of sturgeon juveniles. FARIA et al (2002), when analyzing (0, 4, 8, 12, 16, and 20%) the inclusion of poultry by-product meal in the diets of Nile tilapia fingerlings, have obtained a quadratic effect, which shows a better conversion for the level of 20% of inclusion. SIGNOR et al (2007) have found (for 0, 5, 10, 15, and 20% of this same ingredient) a linear decrease, and the level of 20% of inclusion of poultry by-product meal resulted in the best feed conversion for Leporinus macrocephalus juveniles.…”
Section: Resultsmentioning
confidence: 94%
“…Entretanto, FARIA et al (2002) estudaram a inclusão de até 20% de farinha de vísceras em rações para tilápias e afirmam que a taxa de eficiência proteica e de retenção de nitrogênio aumentaram linearmente com o aumento dos níveis do ingrediente nas rações o que, segundo os autores, demostra a melhora na utilização da proteína da ração. Estes resultados reforçam a inferência anterior, de que a qualidade da farinha de vísceras utilizada no presente estudo pode ser superior à qualidade daquelas estudadas pelos demais autores citados.…”
Section: Justificaram Os Valores Deunclassified
“…3 El proceso educacional puede ocurrir en el espacio no formal, o sea, aquel que sucede en ambientes y situaciones interactivas en las actividades cotidianas del ser humano, construyendo el conocimiento con la participación de los individuos. 4 Se entiende que en el área de la salud los ambientes que merecen mayor atención educativa son los que atienden al usuario en situaciones de posibles vulnerabilidades como acontece en los Servicios de Embellecimiento de Manos y Pies (SEMP), porque existe la posibilidad de contaminaciones que pueden alcanzar al cliente por el uso de material compartido, por fallas en la desinfección/esterilización, por desconocimiento de las vías de transmisión y por descuido del propio profesional en la utilización de los equipos de protección individual (EPI).…”
Section: Introductionunclassified